2022
DOI: 10.1155/2022/7567630
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Intra-Arterial Blood Pressure Monitoring Improves the Efficiency of Percutaneous Balloon Compression of the Trigeminal Ganglion for Trigeminal Neuralgia

Abstract: Objective. The aim of the study is to explore the characteristics of systolic blood pressure (SBP) and heart rate (HR) changes in patients undergoing percutaneous balloon compression (PBC) for trigeminal neuralgia and analyze the factors that influence the formation of the symbolic pear shape of the balloon, which signifies successful compression. Methods. We retrospectively analyzed the changes in systolic blood pressure (SBP) and heart rate (HR) in 103 consecutive patients with trigeminal neuralgia (TN). Fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Finally, one must be careful to avoid intracerebral hemorrhage, during MVD with such high blood pressures [19]. Like our results of improved outcomes in patients with blood pressure spikes, Zuo et al reported that developing intra-operative HTN during BCR meant that the compression was successful, and further supported the use of continuous intra-operative blood pressure monitoring [20].…”
Section: Discussionsupporting
confidence: 70%
“…Finally, one must be careful to avoid intracerebral hemorrhage, during MVD with such high blood pressures [19]. Like our results of improved outcomes in patients with blood pressure spikes, Zuo et al reported that developing intra-operative HTN during BCR meant that the compression was successful, and further supported the use of continuous intra-operative blood pressure monitoring [20].…”
Section: Discussionsupporting
confidence: 70%